2010
DOI: 10.1021/bm9014039
|View full text |Cite
|
Sign up to set email alerts
|

Sterilized Recombinant Spider Silk Fibers of Low Pyrogenicity

Abstract: We have recently shown that it is possible to recombinantly produce a miniature spider silk protein, 4RepCT, that spontaneously self-assembles into mechanically stable macroscopic fibers (Stark, M.; Grip, S.; Rising, A.; Hedhammar, M.; Engstrom, W.; Hjalm, G.; Johansson, J. Macroscopic fibers self-assembled from recombinant miniature spider silk proteins. Biomacromolecules 2007, 8 (5), 1695-1701). When produced as a soluble fusion protein (with thioredoxin) in Escherichia coli , the spider silk protein can be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
66
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 55 publications
(68 citation statements)
references
References 28 publications
2
66
0
Order By: Relevance
“…The development of sophisticated porous scaffolds for use in 45 tissue engineering applications requires the careful choice of scaf- 46 fold properties, as the requirements for the materials are explicit 47 for the specific tissue to be regenerated. Scaffold morphology and 48 topology, crystallinity and scaffold stiffness are amongst the 49 parameters that have been shown to influence the ability of cells 50 to attach, produce extracellular matrix and form a complex tissue 51 construct [1]. Such porous three-dimensional (3-D) scaffolds used 52 in tissue engineering must also be safe for clinical use.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The development of sophisticated porous scaffolds for use in 45 tissue engineering applications requires the careful choice of scaf- 46 fold properties, as the requirements for the materials are explicit 47 for the specific tissue to be regenerated. Scaffold morphology and 48 topology, crystallinity and scaffold stiffness are amongst the 49 parameters that have been shown to influence the ability of cells 50 to attach, produce extracellular matrix and form a complex tissue 51 construct [1]. Such porous three-dimensional (3-D) scaffolds used 52 in tissue engineering must also be safe for clinical use.…”
mentioning
confidence: 99%
“…In both cases, be-501 sides the degrading effects, the porous structures were destroyed 502 as a consequence of plastic deformation from the heat treatment 503[48]. A recent study on recombinantly produced miniature spider 504 silk protein fibers suggested that the known stability of silk might 505 be an advantage in this regard too[49]. Our study confirms that 3-506 D scaffolds made of SF from regenerated B. mori L. cocoons can 507 structurally withstand the heat treatment experienced with heat 508 sterilization or autoclaving.…”
mentioning
confidence: 99%
“…Several strategies to avoid these problems have been tried, such as the introduction of methionine residues for controlled oxidation/reduction to prevent and promote assembly, respectively [50,65,89], kinase recognition motifs for controlled assembly via enzymatic phosphorylation [54] or solubility-enhancing fusion partners that can be released enzymatically [11]. In the latter case, spontaneous assembly into macroscopic, sterile, pyrogen-free and biocompatible silk-like fibres is possible, with the use of only physiologically compatible solvents [11,90,91] (Fig. 2).…”
Section: Recombinant Spidroin Productionmentioning
confidence: 99%
“…Affinity purification usually yields recombinantly produced proteins with over 90% purity, but a significant amount of endotoxins is retained. A production route that combines purification of a minispidroin (4Rep-CT; Table 3) and endotoxin removal by using a simple cell wash procedure, protein affinity purification and LPS depletion has recently been developed [91]. Applying this method, it was possible to produce fibres with in vitro pyrogenicity corresponding to less than 1 EU/mg; the fibres could be sterilized by autoclaving, and human primary fibroblasts were shown to grow on them [91] (Fig.…”
Section: Spider Silk For Cell Support and Implantationmentioning
confidence: 99%
“…15 Gram positive bacteria, e.g., Bacillus subtilis and Staphylococcus aureus, lack an outer membrane (and therefore LPS), which simplifies secretion of recombinant proteins. 16 However, the pathogenic nature of e.g., S. aureus 17 requires extra caution if used as host for production of biomaterials.…”
Section: Production Of Spidroins In Heterologous Hostsmentioning
confidence: 99%